"Recovering" public space and race: Afro-Colombian street vendors in Bogotá, Colombia. (June 2018) - Munoz, Lorena
Bogotá, Colombia is one of the largest migrant-receiving cities in the Americas, and in the last two decades, the city has received an influx of over one million people displaced by internal violent political conflicts. Currently, the Afro-Colombian population constitutes approximately 10% of the total population, but continues to be highly concentrated in the lowest socioeconomic strata in the Pacific region of Colombia. Informal vending in Bogotá is comprised of primarily rural and/or internally displaced migrants, including Afro-Colombians and indigenous populations who journey to large urban centers in search of better education and income opportunities and a higher quality of life. In this paper, I argue that Afro-Colombians endure higher marginality and discrimination as street vendors than self-identified as mestizos. Thus, Black bodies are multiple marked by discourses of crime, displacement, and undesirability in public spaces. In addition, street vending in Bogotá is understood by urban scholars as well as the local state as a classed struggle, this understanding through class effectively deracializes the informal vending landscape, while also further reifying the invisibility of Black racialized bodies in Bogotá's equality discourses. The failure to recognize the diverse racial makeup of informal vendors and understanding these struggles only through class obscure the social and economic realities encountered by racialized bodies in public space.